INDUSTRIAL PLANNING SITE FORMAT AND OBJECTIVES - Al-Shammari, Wafaa Kadhim; Atiyah, Ola Abed; Kadhim, Buraiha Saad (Antis-Publisher, 2026)
Objective: This study aims to examine industrial planning as a scientific approach to organizing interconnected industrial processes within a strategic framework to achieve sustainable economic development. Method: The research employs a descriptive-analytical method, integrating literature review and contextual analysis to evaluate industrial planning tools and techniques, particularly in localizing industries by selecting suitable locations for industrial centers and ensuring alignment with environmental and economic conditions. Results: Findings indicate that industrial planning not only enhances the economic value of projects by determining optimal industrial locations but also supports the development of industrial complexes and warehouses, responding to evolving production methods and maximizing industrial returns. However, the process faces critical environmental, economic, and political challenges that hinder its effectiveness. Novelty: The study contributes by highlighting industrial planning as a comprehensive model that balances industrial growth with environmental compatibility, offering new insights into how planners can mitigate challenges while reinforcing industry’s central role in strengthening national economies and improving societal welfare.